Modeling potential distribution of the Nguyen's Fanged Frog Limnonectes nguyenorum - Van Anh, Pham; Quang Truong, Nguyen; Duc Minh, Le; The Cuong, Pham; Tuan Anh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3DO - 10.25073/2588-1094/vnuees.4980, 2023)
The Nguyen’s Fanged Frog (Limnonectes nguyenorum) was originally discovered from Vietnam in 2015, and it was recently recorded in China in 2021. In Vietnam, this species has been recorded  in Ha Giang, Tuyen Quang, Lao Cai, Yen Bai, Son La, and Vinh Phuc provinces. Although information on ecology and distribution of the Nguyen’s Fanged Frog is still limited, hunting for food and habitat destruction are major threats to the populations of L. nguyenorum. In this study, we used species occurrence data from previous studies and our field surveys to predict the potential distribution of the species using MaxEnt approach. The model results show that the potential distribution of L. nguyenorum may include other national parks and nature reserves in northern Vietnam: Hoang Lien – Van Ban and Bat Xat (Lao Cai); Muong La and Ta Xua (Son La); Che Tao and Na Hau (Yen Bai); Xuan Son (Phu Tho); Tam Dao (Vinh Phuc-Thai Nguyen-Tuyen Quang); Na Hang (Tuyen Quang); Ba Be (Bac Kan); as well as Bac Me, Du Gia, Phong Quang, and Bat Dai Son (Ha Giang). Based on the optimal model the predicted populations of the Nguyen Fanged Frog in Xuan Son and Tam Dao national parks in Vietnam, and Daweishan in Yunnan Province of China, if exists, may represent unique evolutionary clades. Therefore, future research and conservation initiatives may focus their efforts in such areas to find new populations of the Nguyen’s Fanged Frog, as well as assess the distribution, habitat, and ecological patterns of this newly discovered amphibian species .